Across Central Asia: cultural crossroads, religious interactions? : The Monastery, H.2153 fol. 131v, Topkapı Sarayı Müzesi, Istanbul - Fazio, Nicoletta (The dynamics of transculturality, 2015)
What can paintings tell us about the past they pretend to depict, no matter how faithfully or fancifully, and the breadth of life they hide under a brilliant and dazzling surface? Today historians understand the image to be a helpful research tool since it is clear that the reading of the past passes not only through texts but also through the images it produced. This paper analyses an intriguing, yet enigmatic, miniature painting that was presumably produced in Aq Qoyunlu Tabriz around the end of fifteenth century and is currently pasted onto a page in the famous album H.2153 (Topkapı Sarayı Müzesi, Istanbul). Conventionally known as The Monastery by historians of Islamic art, the painting depicts a beautifully decorated polygonal building hosting a puzzling community of learned men, beggars, mystics, women, and children who appear to live together in an atmosphere of religious tolerance, study, and reciprocal understanding. Many readings of the painting have been attempted since the 1980 conference ‘Between Iran and China’ (Percival David Foundation, London), and yet no agreements have been reached on its interpretation. Was it a ‘utopian’ artist’s dream, a complex style exercise for the practices developed in a royal kitabkhana, or perhaps a ‘realistic’ representation of an actual place? Although this short article cannot provide final answers to these questions, through an artistic and historical analysis it aims to demonstrate the dynamic richness of life on the borders, (i.e. in Central Asia) where different cultures and creeds met to create phenomena of hybridization.
First Online: 10 October 2014
Gesehen am 02.06.2020